Peculiarities of dry adygh “Mate” cheese and its use in the production of culinary products in the conditions of import substitution - Z. N. Khatko; A. B. Tkhaishaova; M. A. Gasheva (Новые технологии)
The article presents the results of studies on the quality of dried (dry) Adyghcheese based on sensory evaluation of control samples of cheese; physicochemical indicators and safety indicators of the product have been determined. The authors substantiate the possibility of using Adygh dried (dry) "Mate" cheese in the production of culinary products. Innovative dishes have been developed: "Medallions with cheese sauce", "Salmon with “Mate” sauce, “Omelette with “Mate” cheese”.